Initial Validation of the Psychobiosocial States in Physical Education (PBS-SPE) Scale - Bortoli, Laura; Vitali, Francesca; Di Battista, Rossana; Ruiz, Montse C.; Robazza, Claudio (Frontiers in Psychology, 2018)
The purpose of this cross-sectional investigation was to examine the item characteristics, factor structure, reliability, convergent validity, and construct validity of the Psychobiosocial States in Physical Education (PBS-SPE) scale. In Study 1, a sample of 1,030 students (582 girls and 448 boys, 10 to 19-year-olds), drawn from middle or high schools, rated the intensity of the 20 items version of the PBS-SPE scale thinking about the feelings they had usually experienced in physical education classes. In Study 2, an additional sample of 1,025 students (578 girls, 447 boys, 10 to 19-year-olds), rated the 16 items of the final version of the scale. Two subsamples also completed an affective-related measure (i.e., the Physical Activity Enjoyment Scale) and two motivation scales often used in the physical education domain (i.e., the Teacher-Initiated Motivational Climate in Physical Education Questionnaire and the Situational Motivation Scale). Exploratory structural equation modeling and confirmatory factor analyses of the data showed that a two-factor, 16-item solution (i.e., 8 pleasant/functional items and 8 unpleasant/dysfunctional items) of the PBS-SPE scale reached satisfactory fit indices. Multi-group comparisons provided support for measurement and structural invariance across samples, gender, and age. Convergent and construct validity was also upheld. Overall, the findings offer support for the use of a new instrument in the assessment of psychobiosocial states in physical education settings.